2007
DOI: 10.1159/000112235
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Chronic Disease

Abstract: Growth impairment occurs with many chronic conditions. Cystic fibrosis, Crohn’s disease and juvenile idiopathic arthritis are relatively common chronic diseases in childhood associated with substantial growth impairment. While growth failure may be the initial presenting feature of pathology, the pattern of growth is also a useful measure of disease severity and response to treatment. In addition to its diagnostic value, the resulting short stature cannot only be unacceptable to patients but can also have detr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 117 publications
1
18
0
Order By: Relevance
“…They are influenced by multiple variables such as: genetics, geographic location, climate, psychological factors, socioeconomic status, body weight and height, nutrition, body fat, and exercise, as well as the presence of chronic diseases. 17,18 In our patients, the mean age at menarche was associated with an earlier age at the start of ICT with DFO, lower SF levels, and an average BMI-Z score, and a higher prevalence of regular subsequent menstrual cycles and duration of menstrual history.…”
Section: Menstrual Characteristics and Duration Of Menstrual History In Relation To Bmi And Ictmentioning
confidence: 69%
“…They are influenced by multiple variables such as: genetics, geographic location, climate, psychological factors, socioeconomic status, body weight and height, nutrition, body fat, and exercise, as well as the presence of chronic diseases. 17,18 In our patients, the mean age at menarche was associated with an earlier age at the start of ICT with DFO, lower SF levels, and an average BMI-Z score, and a higher prevalence of regular subsequent menstrual cycles and duration of menstrual history.…”
Section: Menstrual Characteristics and Duration Of Menstrual History In Relation To Bmi And Ictmentioning
confidence: 69%
“…In 1892, Porter conducted a study on 33,500 students and reported that taller students performed better academically than shorter students of the same age (19). Since then, many studies have been carried out examining the association between height and intellectual development.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation could lead to significant growth retardation in children and adolescents [59,[65][66][67][68]. Experimental data indicate that this effect is independent of undernutrition and occurs even in well-nourished patients [28,[69][70][71]. It is also emphasised that the degree of growth retardation correlates with the activity of the inflammatory disease [9].…”
Section: The Effects Of Childhood-onset Chronic Inflammatory Diseasesmentioning
confidence: 99%
“…Those changes usually coexist with normal physiological or stimulated serum GH levels, which confirms a state of GH resistance, but other mechanisms of growth impairment are also considered [9,28,42,38,75,76]. On the other hand, it should be taken into account that IGF-1 as a valuable laboratory indicator of nutritional status could be decreased in states of poor nutrition due to limited nutrient intake and malabsorption, which often accompany chronic inflammation [23,28,69]. Serum levels of IGFBP-3 do not seem to be as dependent on nutritional deprivation as IGF-1, and they better reflect GH signalling [77].…”
Section: The Effects Of Childhood-onset Chronic Inflammatory Diseasesmentioning
confidence: 99%